Development of Numeracy and Literacy-based Probability Teaching Materials - Alfarisy, Hafiz; Awalludin, Subhan Ajiz (Unnes Journal of Mathematics Education, 2023)
The aim of this research was to develop a product based on numeracy skills through teaching materials. This study used a research and development (R&D) methodology approach using the ADDIE model. This research aimed to develop a product based on numeracy literacy through teaching materials. This research used research and development (R&D) with the ADDIE model. The participants in this study were categorized into two groups, large groups and small groups of grade 10 from SMAN in one of the cities of East Jakarta. Data collection included an expert test with three expert validators, material, media, and language, and an interview and student response questionnaire. The results of product development form teaching materials based on numeracy literacy using Flip PDF Corporate Edition. The results from material expert, media expert, and linguist expert validation obtained an average score of with the category "Excellent". As a result, it can be concluded that teaching materials based on numeracy literacy are eligible for use as teaching materials probability.